2012
DOI: 10.1007/s10965-011-9802-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of optically active poly(amide-imide)/TiO2 bionanocomposites containing N-trimellitylimido-L-isoleucine linkages: using ionic liquid and ultrasonic irradiation

Abstract: In the present investigation, novel poly(amideimide)/TiO 2 bionanocomposites containing L-isoleucine moiety in the main chain were prepared via a simple and inexpensive ultrasonic irradiation process. Poly(amide-imide) as a source of polymer was synthesized by direct polycondensation reaction of N-trimellitylimido-L-isoleucine with 4,4′-diaminodiphenylsulfone in the tetrabutyl ammonium bromide/triphenyl phosphite as a green solvent system. Due to the high surface energy and tendency for agglomeration, the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Also the surface of TiO 2 NPs modified with KH550 [99][100][101]. In another study, Mallakpour and Dinari [102] reported the modification of Al 2 O 3 with KH550 coupling agent.…”
Section: Silanesmentioning
confidence: 98%
“…Also the surface of TiO 2 NPs modified with KH550 [99][100][101]. In another study, Mallakpour and Dinari [102] reported the modification of Al 2 O 3 with KH550 coupling agent.…”
Section: Silanesmentioning
confidence: 98%
“…For TiO 2 nanoparticle, the broad peak at 3,449 cm 21 corresponds to stretching motions of the surface hydroxyl or the adsorbed water and the peak at 1,634 cm 21 corresponds to vibration of OAH bonds on the TiO 2 nanoparticles surface. The broad band observed in the region 825 cm 21 corresponds to TiAO stretching peak [28].…”
mentioning
confidence: 97%
“…The compatibility between water‐soluble resin and nano‐particle was a problem for the water‐based composite electrical steel coating. So it is a great chance to deal the problem, as a result the nano‐particles were always modified to enhance the compatibility , such as modified by silance coupling agent , titanate coupling agent, or grafted by polymer . In the present paper, glycine was used to graft the SiO 2 nano‐particles in the study, and the compatibility between the polyester solvent and the SiO 2 particles was enhanced.…”
Section: Introductionmentioning
confidence: 92%